Strategic Management and Firm Survival - Supangkat, Hendrarto; Widiana, Rina (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2022)
Strategic management has been praised for presenting firms with advantages. However, there is still a lack of empirical evidence for its impact on firms in difficult conditions. This study evaluates a unique situation in which firms facing the same external threat could end up differently. The relationships between strategic management and firms’ abilities to survive were investigated through a survey of 67 nickel-mining firms in Sulawesi Island, Indonesia. Each firm’s level in strategic management was measured by a questionnaire, which is based on a two-dimensional model for strategic management maturity comprising process and leadership dimensions. Meanwhile, a firm’s survival ability was assessed in six facets, including the ability to detect a threat, formulate an anticipation plan, implement the plan, maintain operations, maintain performance, and continue to exist in the future. Regression techniques were employed in the analysis. Proof of the positive effect that strategic management has on firms’ survival is delivered as the main result. It is further found that maturity in the strategic management process plays a more dominant role than strategic leadership. The effects of both dimensions in strategic management maturity on each survival ability facet are also explored.